Improvement of Discharge Flow Structure by Bluff-Body Insert and Size Reduction of a Mixed-Flow Irrigation Pump - Wasinarom, Kittipass; Boonchauy, Dachdanai; Noosomton, Jaruphant; Charoensuk, Jarruwat (My University, 2022)
This paper concerns efficiency improvement of an 8-in. mixed-flow irrigation pump by modification of discharge flow channel. First, computational fluid dynamics (CFD) modeling was validated with the experimental results using an available pump. Next, an investigation on the hydrodynamics structure was carried out by CFD. The investigation revealed large recirculation around the inner annulus area next to the impeller exit plane and jet flow around the pipe wall. This leads to formation of a strong shear layer between jet and recirculation flow. Improvements were realized by reducing the impeller size by 10% to increase the flow cross-sectional area between the impeller exit plane and the tube wall to slow down the jet flow. Bluff body was introduced at the inner annulus adjacent to the discharge flow channel to alleviate a recirculation wake region. The operating speed of the scaled-down impeller was increased from 900 to 1,100 rpm to compensate for the scaling effect, and the blade angle was modified to cope with the change of inlet relative flow angle. Experimental study suggested that more than 10% improvement could be achieved through these modifications. The maximum efficiency of the proposed model was 42%, compared with the maximum efficiency of 37% for the conventional model.
Keywords: Hydrodynamics; Irrigation pump; Mixed flow; Pump efficiency improvement; Pump hydrodynamics